Mencerna Akar Filsafat dalam Islam - Ismail Fahmi Arrauf (Ulumuna, 2013)
Philosophizing by philosophers is logical, independent, systematic, radical, and universal thinking on anything. Researchers have long been interested in investigating Islamic Philosophy, as a branch of science that develops later and commonly known as one rooted from Greece. This paper then aims at investigating the extent Islamic Philosophy interconnects with Greek Philosophy as well as their differences. Methods employed at this research are identifying Qur’an verses on Philosophy, and enriching them to reviews of related literature. Important findings are Islamic Philosophy is mainly derived from Qur’an values, its interconnectedness with Greek Philosophy does not mean it is integrated, and apart from different views on Philosophy, arguments where Qur’an reveals values of Philosophy is highlighted.